2010
DOI: 10.1128/jcm.02072-09
|View full text |Cite
|
Sign up to set email alerts
|

Noroviruses as a Cause of Diarrhea in Travelers to Guatemala, India, and Mexico

Abstract: Noroviruses (NoVs) are increasingly being recognized as an important enteric pathogen of gastroenteritis worldwide. The prevalence of NoVs as a cause of diarrhea acquired by travelers in developing countries is not well known. We examined the prevalence and importance of NoV infection in three international traveler cohorts with diarrhea acquired in three developing regions of the world, Mexico, Guatemala, and India. We also characterized the demographics and symptoms associated with NoV diarrhea in these trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 28 publications
4
30
1
Order By: Relevance
“…This observation is in line with our previous studies in travelers where rates of co-infections are found to be over 60% 7 . TD is characterized as multifactorial disease caused by a wide range of enteric pathogens including bacteria, viruses and parasites 24 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This observation is in line with our previous studies in travelers where rates of co-infections are found to be over 60% 7 . TD is characterized as multifactorial disease caused by a wide range of enteric pathogens including bacteria, viruses and parasites 24 .…”
Section: Discussionsupporting
confidence: 94%
“…NoVs are highly infectious, very stable and remarkably transmissible 4, 5 . Besides being a leading cause of epidemic acute gastroenteritis and an important cause of hospital acquired and sporadic infection, NoVs have also been described as a common etiology of travelers’ diarrhea (TD) 6, 7 . Interestingly, TD studies over time and in different locations have reported a marked diversity of GI- and GII-NoVs among cases 6, 8–10 .…”
mentioning
confidence: 99%
“…In the United States, NoVs cause 19 to 21 million cases each year (4,5). NoV outbreaks have been identified in children (6), the elderly (7), military personnel (8,9), immunocompromised individuals (10), restaurant patrons (11,12), travelers to developing countries (13,14), passengers of cruise ships (15), residents of health care facilities such as nursing homes (16,17) and hospitals (18), and other populations housed in close quarters (19). The increasing incidence of NoV infections emphasizes the need to quickly detect and identify the causative agent, because early diagnosis of NoV infection can be crucial in the effective control of outbreaks and can decrease the secondary attack rate (20).…”
mentioning
confidence: 99%
“…nursing homes but also on cruise ships. It has been detected as a cause of TD in up to 10-17% of travelers from different countries (Apelt et al, 2010;Hill and Beeching, 2010;Koo et al, 2010). Studies reporting prevalences as high as 65% have been published (Chapin et al, 2005).…”
Section: Viruses As Causative Agents In the Development Of Tdmentioning
confidence: 99%